<span> i'm going to be slightly extra careful in showing each step. specific, ln [n / (n+a million) ]= ln n - ln(n+a million). So, we've sum(n=a million to infinity) ln [n / (n+a million) ] = lim(ok--> infinity) sum(n=a million to ok) ln [n / (n+a million) ] = lim(ok--> infinity) sum(n=a million to ok) [ln n - ln(n+a million)] = lim(ok--> infinity) (ln a million - ln 2) + (ln 2 - ln 3) + ... + (ln ok - ln(ok+a million)) = lim(ok--> infinity) (ln a million - ln(ok+a million)), for the reason that fairly much all the words cancel one yet another. Now, ln a million = 0 and lim(ok--> infinity) ln(ok+a million) is countless. So, the sum diverges to -infinity. IM NOT COMPLETELY SURE
</span>
Answer:
a)
Step-by-step explanation:
for each point (A, B, C) reduce the 'x-value' by two and reduce the 'y-value' by 7
for example, for point A:
to find A': (-6, -7) would be (-6-2, -7-7) which is (-8, -14)
Answer:
The simplified form of expression<u> </u>(-2 - 8x) + (-4x - 10) is
-12(x + 1)
Step-by-step explanation:
It is given an expression (-2 - 8x) + (-4x - 10)
<u>To find the simplified expression of (-2 - 8x) + (-4x - 10)</u>
Let expression is given by
(-2 - 8x) + (-4x - 10) = -2 - 8x -4x -10
= -2 -10 -4x -8x
= -12 -12x
-12(x + 1) (since -12 is common in both terms)
Therefore simplified form is -12(x + 1)
In two years tom will become 10 years old
Because 5×2=10